Peran Hukum Adat Dalam Penyelesaian Persoalan Adat di Desa Didiri Kecamatan Pamona Timur - Taroreh, Erwin; Fadilah Husain; Zulfa Cika Ananda Wenur (Dinasti Review Publisher, 2024)
The result of implementing centralization so far is dissatisfaction from both the community and the conflicting parties (in this case the perpetrator and the victim). It is a real reality that national law cannot necessarily guarantee the justice desired by all parties, and cannot necessarily restore the condition of society damaged by the conflict. National law is only guided by how to protect society, without looking at whether the interests of society and the conflicting parties have been protected. For people in each region who still adhere to customary rules, conflict resolution using customary law is felt to guarantee justice and have more value than national law which tends to be less impartial. This is because customary law is a collective agreement of the local community which has taken into account the interests of the community, individuals and conflicting parties.